Use of Cytopoint in the Allergic Dog - Gober, Margaret; Hillier, Andrew; Vasquez-Hidalgo, Manuel A.; Amodie, Deborah; Mellencamp, Martha A. (Frontiers in Veterinary Science, 2022)
Allergic dermatitis is the most common type of skin disease in dogs. Of all dogs, 20% to 30% present with some type of allergic dermatitis. Pruritus is one of the most important signs of allergic dermatitis and is often the most challenging to control. Interleukin-31 (IL-31) has been found to be one of the main causes of pruritus in dogs with allergic dermatitis. Cytopoint®, a caninized monoclonal anti-IL-31 antibody, has been approved for the treatment of canine allergic and atopic dermatitis. A recent retrospective study reported that Cytopoint achieved treatment success in 87.8% of the cases with allergic dermatitis. No prospective/cohort studies have been performed investigating the effects of Cytopoint in dogs with allergic dermatitis using the dosing protocol prescribed on the product label in the United States. In this study, our objectives were to assess the efficacy of Cytopoint for treatment of canine allergic dermatitis of variable etiologies and management of the associated pruritus. Dogs included in this study had moderate to severe pruritus according to the Pruritus Visual Analog Scale (PVAS; ≥ 50 mm) and a history of likely continuation of itch at the time of presentation. On day 0, investigators recorded the initial body weight and every patient received one dose of Cytopoint (minimum 2 mg/kg SQ) and an isoxazoline product for parasite control. Treatment success for this study was defined as a ≥20 mm reduction in PVAS from Day 0. On Day 7, 94% of the dogs had achieved treatment success. On Day 28, 98% had achieved treatment success and cumulatively by day 56, 100% of the dogs achieved treatment success. This prospective study provides evidence that Cytopoint effectively treats dogs with allergic dermatitis of different types and the associated pruritus.